Does your city need a metro? – A Tel Aviv case study. Issue 4 (December 2018) - Sharav, Nir; Szeinuk, Marcos; Shiftan, Yoram
Highlights: A methodological approach to determine the need and level of transit investment. This can help decision makers set strategic goals and decide about the transit investments. The future transit network in Tel Aviv needs major investments to upgrade to a metro network. Abstract: Planning and investing in a transit system to provide future mobility needs in a growing metropolitan area is a complex mission requiring a long-term strategic outlook and major financial investment. The objective of this paper is to demonstrate a methodological approach that combines indicative and strategic long-term tools with detailed transport planning and network simulations to evaluate needs for investment in urban transit, plan the transit network structure and determine the investment requirements. The methodology enables the policy maker to focus on the overall approach to the direction of system development and its effect on mobility. It consists of scenario settings, network structure and mode planning along with an evaluation process that both ranks strategic goals and utilizes an activity-based transportation model for more detailed analysis. The approach is demonstrated in a case study of Tel Aviv, the largest metropolitan area in Israel, where current transportation services are provided mainly by buses and limited suburban rail routes. This paper shows the value of the methodology to determine the city's transit needs. In conclusion, the paper determines that the future Tel Aviv transit system will require an extensive investment in a metro-oriented network in order to provide the city's mobility needs along with the desirable level of service and transit usage. The result of this paper illustrates how this approach can help decision makers set strategic goals and make decisions regarding their city's future transit system to meet mobility needs.